Evolutionary Dynamics of the Repetitive DNA in the Karyotypes of Pipa carvalhoi and Xenopus tropicalis (Anura, Pipidae) - Zattera, Michelle Louise; Gazolla, Camilla Borges; Soares, Amanda de Araújo; Gazoni, Thiago; Pollet, Nicolas; Recco-Pimentel, Shirlei Maria; Bruschi, Daniel Pacheco (Frontiers in Genetics, 2020)
The amphibian genomes contain numerous repetitive DNA components that have played an important role in the karyotypic diversification of this group. Hypotheses based on the primitive karyotype (2n=20) of the family Pipidae suggest that they have evolved principally through intrachromosomal rearrangements. Pipa is the only South American pipid, while all the other genera are found in Africa. The divergence of the South American lineages from the African ones occurred at least 136 million years ago and is thought to have had a strong biogeographic component. Here, we tested the potential of the repetitive DNA to better understand the differentiation of the karyotype among the family Pipidae and to expand our capacity of the interpretation of the chromosomal evolution in this family. Our results indicate a long history of conservation in the chromosome bearing the H3 histone locus, corroborating inferences on the chromosomal homologies between the species in pairs 6, 8 and 9. The chromosomal distribution of the microsatellite motifs also provide useful markers for comparative genomics at the chromosome level between species, contributing new insights into the evolution of the karyotypes of these species. We detected similar patterns in the distribution and abundance of the microsatellite arrangements, which reflect the shared organization in the terminal/subterminal region of the chromosomes between these two species. By contrast, the microsatellite probes detected a differential arrangement of the repetitive DNA among the chromosomes of the two species that allow longitudinal differentiation of the pairs that are identical in size and morphology, such as pairs 1, 2, 4, and 5. We also found evidence of the distinctive composition of the repetitive motifs of the centromeric region between the species analyzed in the present study, with a clear enrichment of the (CA) and (GA) microsatellite motifs in P. carvalhoi. Finally, microsatellite enrichment in the pericentromeric region of chromosome pairs 6, 8 and 9 in the P. carvalhoi karyotype, together with interstitial telomeric sequences, validate the hypothesis that pericentromeric inversions occurred during the chromosomal evolution of P. carvalhoi and reinforce the role of the repetitive DNA in the remodeling of the karyotype architecture of the Pipidae.